The politics and poetics of memory: law and temporality in contemporary Egypt - El Sheikh, Mayy (AUC Knowledge Fountain, 2020)
Eight years have passed since the 25th of January revolution in 2011 which succeeded in removing former President Hosni Mubarak after 30 years in power. Initially, the revolution was hailed for its promise of democratization and its anticipated positive impact the condition of human rights. Today, Egypt is under military authoritarian rule and the human rights situation is worse than it has ever been in the country's modern history. This thesis investigates the role of law in Egypt's current wave of tyranny and how it contributed to, rather than stood up against, the failure of the revolution's promise. This thesis looks at law at the heart of the rising tide of tyranny in today's Egypt to make an argument about memory as an object of power and to examine the role of law in this relationship. This examination reveals that the Egyptian state is ruling by law, and is using memory as one of its key instruments in the production of subjects with violable bodies.